Utilização de matérias primas vegetais para aplicabilidade como inibidores de corrosão - Anjos, Gineide Conceição dos (2012)
In the search for products that act as corrosion inhibitors and do not cause environmental, impact the use of plant extracts as corrosion inhibitors is becoming a promising alternative. In this work the efficiency of polar extracts (ethanol extracts) obtained from the plants Anacardium occidentale Linn (AO) and Phyllantus amarus Schum. & Thonn (PA) as corrosion inhibitors were evaluated in different concentrations. For that AO and PA extracts were solubilized in the microemulsion systems (SME) containing saponified coconut oil as surfactant (SME -OCS and SME-OCS-1) in saline (NaCl 3,5 %) solution, which was also used as electrolyte. Both SME-OCS and SME-OCS-1 were characterized by surface tension and viscosity methods showing a Newtonian fluid behavior. The SME-OCS and SME-OCS-1 systems satisfactorily solubilized the polar extracts AO and PA with measurements carried out by ultraviolet spectroscopy. The measurements of corrosion inhibition efficiencies were performed by the electrochemical linear polarization resistance (LPR) technique as well as weight loss, on the surface of AISI 1020 carbon steel. The maximum corrosion inhibition efficiencies were determined by extrapolation of Tafel plots, showing the following values: 95,6 % for the system SME-OCS-AO, 98,9 % for the system SME-OCS-AO-1 and 93,4 % for the system SME-OCS-PA